2019
DOI: 10.1002/cctc.201801897
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Dehydrogenation of Formic Acid with Ruthenium‐PNP‐Pincer Complexes: Comparing N‐Methylated and NH‐Ligands

Abstract: Complexes Ru(H)(Cl)(CO)(HN{CH2CH2P(iPr)2}2) 7 and Ru(H)(Cl)(CO)(CH3N{CH2CH2P(iPr)2}2) 8 were compared for the selective dehydrogenation (DH) of formic acid (FA) at different pH values. Remarkably, highest activities were observed in acidic environment (pH 4.5). Under all investigated conditions, the N‐methylated complex 8 showed improved performance compared to 7. These observations can be mechanistically explained with protonation of 4H/3Me being the key step in formic acid DH for both complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 50 publications
(9 reference statements)
1
39
0
Order By: Relevance
“…In contrast to the bifunctional out‐sphere mechanism, the PNP−Co system showed that although N−H functional group was not directly involved in the H 2 formation. While the N−H group can assist the elimination of Co−H via hydrogen bonding of N−H⋅⋅⋅OOCH, the team found the catalytic activity was improved by replacing N−H with N−Me in a PNP−Ru analog 24 …”
Section: Catalysts With a Pincer‐type Ligandmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the bifunctional out‐sphere mechanism, the PNP−Co system showed that although N−H functional group was not directly involved in the H 2 formation. While the N−H group can assist the elimination of Co−H via hydrogen bonding of N−H⋅⋅⋅OOCH, the team found the catalytic activity was improved by replacing N−H with N−Me in a PNP−Ru analog 24 …”
Section: Catalysts With a Pincer‐type Ligandmentioning
confidence: 99%
“…While the NÀ H group can assist the elimination of CoÀ H via hydrogen bonding of NÀ H···OOCH, the team found the catalytic activity was improved by replacing NÀ H with NÀ Me in a PNPÀ Ru analog 24. [44] Scheme 3. Suggested FA dehydrogenation mechanism with Berben's Aluminium catalyst.…”
Section: Catalysts With a Pincer-type Ligandmentioning
confidence: 99%
“…Interestingly, Olah and Prakash compared the catalytic behavior of [Ru( Ph P Me N Ph P)(CO)ClH] and [Ru( Ph P H N Ph P)(CO)ClH] (TOF of 430 and 298, respectively). Similar results were obtained by us, using [Ru( iPr P Me N iPr P)(CO)ClH] and [Ru( iPr P H N iPr P)(CO)ClH], which reached TOF's of 9219 h –1 and 2573 h –1 , respectively empathizing the superiority of methylated PNP ligands for the Ru catalyzed FA DH. Furthermore, κ 3 ‐( tBu P H N py N H N tBu P) ruthenium complexes were described as active for the formic acid dehydrogenation by Zheng and Huang (TOF of 2380 h –1 ) as well as Pidko (TOF = 257000 h –1 reached in continuous flow) .…”
Section: Introductionmentioning
confidence: 99%
“…This work attracted our attention and we anticipated an interesting ligand feature in the Ru catalyzed FA DH with this cyclometalated κ 3 ‐CNN ruthenium complex. Inspired by this and our recent work regarding ruthenium catalyzed decomposition of FA with a [Ru( iPr P Me N iPr P)(CO)ClH] catalyst, we investigated the potential of this TH catalyst for FA DH leading to H 2 and CO 2 (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…[8b] Thus, formic acid accumulates in the system, with the consequences of lower efficiency and potential danger of "killing"t he catalystw ith too much acid. [13] Hence, the key to improvement of methanol DH lies in the improved conversion of formic acid. One possibility to achieve this goal is the addition of as econd catalyst, which is especially active for formic acid DH.…”
Section: Introductionmentioning
confidence: 99%